Clinical manifestations and treatment strategies for congenital aural atresia with temporomandibular joint retroposition: a retrospective study of 30 patients - Lin Yang; Peiwei Chen; Yujie Liu; Jinsong Yang; Shouqin Zhao (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients with congenital aural atresia (CAA) can present with concomitant temporomandibular joint (TMJ) retroposition, implying that even with a high Jahrsdoerfer score, canaloplasty and tympanoplasty cannot be performed. Therefore, this study aimed to summarize the clinical manifestations and share our diagnostic and treatment experience of this rare entity, which has not been described previously. Methods Thirty patients (30 ears) with CAA and TMJ retroposition without maxillofacial dysplasia were included. Diagnosis was based on patient history, physical examination, pure-tone average test results, and temporal bone high-resolution computed tomography (HRCT) findings. Their Jahrsdoerfer scores and interventions were also recorded. Results Twenty-four and six patients among the 30 patients (males, n = 15) had CAA and TMJ retroposition on the right and left sides, respectively. Seventeen ears had a normal auricle; most had an enlarged cavum conchae and a large tragus. Twelve ears had an accessory auricle, and two had a preauricular fistula. All external auditory canals had complete atresia, including four with a shallow concavity and four with a small orifice in the cavum conchae. Temporal bone HRCT revealed poor or undeveloped tympanic temporal bone in the diseased ears, atresia in the external auditory canals, and partial/complete occupation of the mandibular condyle with or without soft tissue. The average Jahrsdoerfer score was 8.17. Thirteen patients opted for different surgeries, three wore a bone-conduction hearing aid, and fourteen chose no intervention. Conclusions CAA with TMJ retroposition was often unilateral, typically on the right side. Most patients had normal auricles, with an enlarged cavum conchae and a large tragus (“mirror ear”). Even with a high Jahrsdoerfer score, traditional hearing reconstruction surgery could not be performed. Patients can undergo Vibrant Soundbridge or Bonebridge implantation or wear bone-conduction hearing aids to improve hearing levels, or refuse intervention because of mild hearing loss. The TMJ location can be used as a Jahrsdoerfer Grading System supplement for preoperative evaluation. Graphical Abstract